Bevacizumab-refractory radiation necrosis with pathologic transformation of benign meningioma following adjuvant gamma knife radiosurgery: A rare case report. Issue 31 (31st July 2020) - Kim, You-Sub; Jang, Woo-Youl; Lee, Kyung-Hwa; Moon, Kyung-Sub; Jung, Tae-Young; Jung, Shin
Abstract: Rationale: Bevacizumab has shown good efficacy in radiation necrosis (RN) following gamma knife radiosurgery (GKRS) and associated peritumoral edema. However, few studies have reported bevacizumab failure. Moreover, the pathologic transformation of benign meningioma following GKRS has never been reported. Patients concerns: A 41-year-old man was admitted with focal seizure on the right arm. Diagnoses: Magnetic resonance imaging (MRI) demonstrated a 4.7 cm-sized convexity meningioma involving left motor cortex. Interventions: Subtotally resected tumor was confirmed as a meningothelial meningioma and subsequently treated by GKRS. During 4-year follow-up after GKRS, seizure and hemiparesis had persisted with progressively worsened peritumoral edema regardless of steroid and bevacizumab treatment. Radical debulking of tumor was achieved and immunohistopathological examination revealed angiomatous meningioma with necrotic core presenting scanty VEGF expression. Outcomes: A follow-up MRI at 4 months after debulking surgery showed a marked reduction of peritumoral edema with improvement of symptoms. Lessons: This is the first report of pathologically confirmed angiomatous transformation following GKRS. Although the pathogenesis is not fully understood, this rare pathologic transformation may be closely related to RN. Also, if bevacizumab is resistant, debulking surgery for reducing tumor burden could be an effective treatment option to control the RN.